Hitler - Fest, Joachim C. 1926-2006 (Classic biography, 2002)
Joachim C. Fest's now classic biography is the first major post-war German study of Hitler. Scholarly yet highly readable, it reconciles these differing views of Hitler, both bringing unique insights into his obsessive, hubristic personality and examining the economic, political and cultural conditions that aided him in his terrifying rise to power.